2017
DOI: 10.1007/978-1-4939-7292-0_8
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Oxygen Status in Arabidopsis Leaves Undergoing the Hypersensitive Response During Pseudomonas Infection

Abstract: When plants are infected with pathogens they defend themselves via various processes. Once such process is the development of the hypersensitive response (HR), a kind of programmed cell death (PCD), in which localized cell death takes place in order to prevent pathogen spread to other part of tissue. The Arabidopsis and Pseudomonas syringae system is one of the best known examples to study the HR. Here we used the VisiSens™ oxygen-imaging system to investigate oxygen distributions in Arabidopsis leaves infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Methods to conduct non-invasive O 2 measurements at high spatial and temporal resolution should promote expansion of plant tissue O 2 research from predominantly studying the effect of submergence into other areas. Areas already under investigation include studying plant O 2 levels in relation to plant development (Weits et al 2019), pathology (Kumari et al 2017) and plant signalling (Weits et al 2021). It has been noted that unravelling tissue O 2 dynamics in plants still lacks behind the mammalian field (Ast et al 2012;Schmidt et al 2018).…”
Section: Measuring O 2 In Plant Tissues: Past Present and Future Appr...mentioning
confidence: 99%
See 1 more Smart Citation
“…Methods to conduct non-invasive O 2 measurements at high spatial and temporal resolution should promote expansion of plant tissue O 2 research from predominantly studying the effect of submergence into other areas. Areas already under investigation include studying plant O 2 levels in relation to plant development (Weits et al 2019), pathology (Kumari et al 2017) and plant signalling (Weits et al 2021). It has been noted that unravelling tissue O 2 dynamics in plants still lacks behind the mammalian field (Ast et al 2012;Schmidt et al 2018).…”
Section: Measuring O 2 In Plant Tissues: Past Present and Future Appr...mentioning
confidence: 99%
“…Complete or even partial submergence affects plant O 2 status due to the 10 000-time slower gas diffusion in water than in air, lower solubility of O 2 in water than in air, light attenuation by flood waters and microorganisms depleting flooded soils of O 2 (Voesenek et al 2006). Studies have also demonstrated that biotic and abiotic factors such as pathogen infection, temperature, salinity, and light conditions affect plant tissue O 2 status (Kumari et al 2017;Chung et al 2019;Koch et al 2022aKoch et al , 2022b. Thus, the lack of an active O 2 distribution system in plants, presence of non-photosynthetic plant tissues, and a number of biotic and abiotic factors affecting tissue O 2 , thereby resulting in substantial internal gradients in molecular O 2 .…”
Section: Introductionmentioning
confidence: 99%